An adaptive assessment and management toolkit for data-limited fisheries. (1st February 2018) - McDonald, Gavin; Campbell, Stuart J.; Karr, Kendra; Clemence, Michaela; Granados-Dieseldorff, Pablo; Jakub, Raymond; Kartawijaya, Tasrif; Mueller, Janelle C.; Prihatinningsih, Puji; Siegel, Katherine; Syaifudin, Yusuf
Highlights: An Adaptive assessment and management toolkit has been developed for data-limited fisheries. The toolkit is a comprehensive package for assessing and managing small-scale fisheries. A simple but powerful open-source toolkit dashboard can be used online or offline. The toolkit can accommodate varying degrees of data availability and multiple indicators. The toolkit was piloted for nine species in Karimunjawa National Park, Indonesia.